Optimal multiobjective design of a vehicle restraint system using pre-acting control: A limiting performance analysis - Moita, Paulo Jorge Pires (2019)
Purpose – The purpose of this paper is to performthe limiting performance analysis of a vehicle restraint system (seat belt) in order to find the optimal control force, and its pre-acting time that minimizes the risk of injury. Design/methodology/approach – A discrete model of the human thorax is used. A multiobjective optimum design problem is formulated in order to minimize the risk of injuries in case of impact. Several injury criteria are minimized and are required to remain below a safety threshold value. Findings – The authors found which of the objectives are contradictory and which are not. Several of the optimal sets of design variables are analyzed and their performance compared to one another. The results are also compared to the case of not taking in account the pre-acting time. As expected, the results in this case are worse. Research limitations/implications – As with all limiting performance analysis, the technological implementation restraints of the control force are not taken into account. As such, the solutions must be considered a benchmark to which the actual solution can be compared to. Practical implications – The limiting performance analysis concept allows us to have a theoretical benchmark to which the real control performance can be compared to. Originality/value – As far as the authors know, the pre-acting time, and its implications on the improvement of the performance of the control system, is an original contribution to the problem the authors tried to solve.